2020
DOI: 10.1002/ange.202005445
|View full text |Cite
|
Sign up to set email alerts
|

Al2Pt für die Sauerstoffentwicklungsreaktion bei der Wasserspaltung: eine Strategie zur Erzeugung von Multifunktionalität in der Elektrokatalyse

Abstract: Die Herstellung von Wasserstoff durch Wasserelektrolyse ist nur möglich, wenn wirksame und stabile Katalysatoren für die Sauerstoffentwicklungsreaktion (Oxygen Evolution Reaction, OER) verfügbar sind. Intermetallische Verbindungen mit genau definierter Kristallstruktur und elektronischen Eigenschaften sowie besonderer chemischer Bindung werden als Vorstufe für neue Werkstoffe vorgeschlagen, die interessante katalytische Eigenschaften aufweisen. Al2Pt kristallisiert im Anti‐Fluorit‐Kristallstrukturtyp und zeigt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…However, a recent HAXPES study has shown, that, although a charge transfer towards an anionic Pt species is expected based on quantum-chemical data, shifts towards formal cationic Pt are visible in binary aluminum platinides. 99 The authors could show, that the QTAIM charges on the Pt atoms correlate with the positive shifts of the Pt 4f binding energies. This was attributed to changes in the Pt 5d orbital occupancies preventing an easy interpretation only based on the shifts of the Pt 4f binding energies in this binary system.…”
Section: Xpsmentioning
confidence: 99%
“…However, a recent HAXPES study has shown, that, although a charge transfer towards an anionic Pt species is expected based on quantum-chemical data, shifts towards formal cationic Pt are visible in binary aluminum platinides. 99 The authors could show, that the QTAIM charges on the Pt atoms correlate with the positive shifts of the Pt 4f binding energies. This was attributed to changes in the Pt 5d orbital occupancies preventing an easy interpretation only based on the shifts of the Pt 4f binding energies in this binary system.…”
Section: Xpsmentioning
confidence: 99%